Severe hyperkalemia in a child with diabetic ketoacidosis: A case report - P Diksha Kaveriappa; S Sumithra; P Y Namratha Upadhya; N Kavitha Bhat (Wolters Kluwer Medknow Publications, 2023)
A 16-year-old boy with type 1 Diabetes Mellitus and autoimmune hypothyroidism presented with Diabetic Ketoacidosis (DKA) and severe hyperkalemia .Renal Function test were normal .Hyperkalemia resolved after increasing insulin infusion from 0.1u/kg /hr to 0.3u/kg/hr.Hyperkalemia in DKA is thought to be due to compromised renal function secondary to hypovolemia. But the higher Insulin rate needed to restore normal potassium level in this case , suggests that insulin deficit in itself could be one of the causes for hyperkalemia in DKA .